(untitled) (Orfeu, 2018)
Most research on musical performance anxiety has considered this in relation to the internal characteristics of the performer, the extent of their preparedness for the performance, and factors in the immediate performing environment. The approach to its alleviation has generally been clinical in nature. Little research has been situated within an explicit overarching conceptual framework. This article proposes a theoretical framework that portrays anxiety within a musical performance context as a process that has an explicit time dimension (pre-, during- and post- performance). The model illustrates the likely processes that occur once a performer agrees to participate in a particular performance and explains how these might give rise to either maladaptive or adaptive forms of performance anxiety. The potential longer-term effects on the performer are also discussed. A detailed description of the model and the theories behind its development is followed by a consideration of model’s implications and potential usefulness for both research and education.